Myosin II dynamics are regulated by tension in intercalating cells - Fernandez-Gonzalez, Rodrigo (2009)
Axis elongation in Drosophila occurs through polarized cell rearrangements driven by actomyosin contractility. Myosin II promotes neighbor exchange through the contraction of single cell boundaries, while the contraction of myosin II structures spanning multiple pairs of cells leads to rosette formation. Here we show that actomyosin cables form at a higher frequency than expected by chance during elongation, indicating that cable assembly is an active process. Multicellular cables are sites of increased mechanical tension as measured by laser ablation. Fluorescence recovery after photobleaching experiments show that myosin II is stabilized at the cortex in regions of increased tension. Myosin II is recruited in response to an ectopic force and relieving tension leads to a rapid loss of myosin, indicating that tension is necessary and sufficient for cortical myosin localization. These results demonstrate that myosin II dynamics are regulated by tension in a positive feedback loop that leads to actomyosin cable formation and efficient tissue elongation.